Improved PI neural network-based tension control for stranded wire helical springs manufacturing. (October 2017) - Zhang, Qi; Wang, Shilong; Zhang, Anrui; Zhou, Jie; Liu, Qing
Abstract: During the winding process of stranded wire helical springs (SWHSs), uneven wire tension always results in high rejection rate and non-compliance service life of SWHSs. Combining the proportion integral neural network (PINN) with a simplified actuator model, this paper presents a new control scheme for the SWHS CNC machine to keep the wire tension uniform. The PINN is improved by introducing an error variance ratio, accounting for the interaction between wires, as a modifying factor in the second hidden layer. The actuator model is simplified based on the analysis of the dynamic characteristics of the actuator. The output value of the improved PINN is transferred into control voltage value by the simplified model. The tension of each wire is controlled by an improved PINN. In order to enhance the control performance, the network parameters are updated using the gradient-based back-propagation method. The validity and consistency of the improved PINN are verified by experiments. The results indicate that (1) the computation load is slight; (2) the rising time of the step response is within 1 s; (3) 89%-96% of tension deviation values of the wire 1 and wire 3 under different process parameters are within 10% of the reference tension value; (4) the standard deviation of the wire 2 with large disturbance is 8.24 N. Compared with other algorithms (incremental PI, multiple PIDNN, PI based particle swarm optimization), the control scheme based on the improved PINN has less computation load, faster response speed and better performance in the time-varying and nonlinear system with larger disturbance. Highlights: The interaction between wire tension in the SWHS CNC machine is analyzed. An error variance ratio accounting for the tension interactions is first introduced to improved performance of the PINN. A novel control scheme with a simplified actuator model is presented based on the improved PINN. The control scheme is easy to implement and performs excellently in the tension control of the SWHS CNC machine.